Effect of 433 MHz double-slot microwave antennas for double-zone ablation in ex vivo swine liver experiment - Xiaofei Jin; Mengwei Jiang; Lu Qian; Ling Tao; Yamin Yang; Lidong Xing; Zhiyu Qian; Weitao Li (PLoS ONE, 2025)
Purpose To evaluate the effects of axial length and slot-to-slot distance of double-slot microwave antenna (DSMA) with frequency of 433 MHz on the size and shape of ablation zones created under different input microwave powers. Materials and methods The design of double slot microwave antennas (DSMAs) with axial lengths (70 mm, 30 mm) and slot-to-slot distance (49 mm, 10 mm) were optimized by numerical simulation and ex vivo liver experiments. Finite-element method simulations and forty ablations of swine liver were employed to obtain the temperature distributions within liver tissue using DSMAs at the 433 MHz operating frequency in a range of heating powers (20, 30, 40 and 50W) for 600 s. The dependence of the effectiveness of MWA on the axial length and slot-to-slot distance of antenna as well as the input power was further evaluated by analyzing morphologic characteristics of ablated zone. Results Two-zone ablation was achieved by two types of double-slot antennas in our study with frequency of 433 MHz, and the observed shapes of ex vivo experimental ablation zones were in good agreement with patterns predicted by simulation models. The ablation zone exhibited a ‘gourd’ shape after the treatment using the antenna with longer axial length and slot-to-slot distance, while the short antenna caused a guitar-shape ablation in liver tissue after MWA. Conclusion The dedicated design of our DSMAs with a frequency of 433 MHz could enable new ablation shapes with controllable dimensions, which can be applied to the clinical treatment of MWA for gourd-shaped liver tumors and other long-shaped tumors. Furthermore, research can be conducted on how to design the antenna as flexible and use it for the treatment of pulmonary nodules or varicose veins.